2018
DOI: 10.12659/msm.909712
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture Therapy for Chemotherapy-Related Cognitive Impairment in Breast Cancer Patients

Abstract: BackgroundChemotherapy can cause adverse effects such as chemotherapy-related cognitive impairment (CRCI). In this prospective study, the efficacy of traditional Chinese medicine acupuncture therapy in relieving CRCI and its impact on serum brain-derived neurotrophic factor (BDNF) are evaluated.Material/MethodsEighty patients were randomly divided into a treatment group and a control group with 40 patients in each group. The treatment group was treated at the following acupuncture points: Baihui (DU20), Sishen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 28 publications
1
65
0
4
Order By: Relevance
“…An increasing number of studies have evaluated the cognitive effects of acupuncture, 85‐88 but to the best of our knowledge few have been conducted in cancer populations. In a randomized controlled trial of 80 Chinese patients with breast cancer who were undergoing chemotherapy, 40 acupuncture significantly improved subjective cognitive function (as measured by the Functional Assessment of Cancer Therapy–Cognitive Function [FACT‐Cog]) and objective cognitive performance (as measured by the Rey Auditory‐Verbal Learning Test and clock drawing test) compared with usual care; however, the durability of these effects after treatment was not assessed. The current study found that acupuncture produced significant, small to moderate improvements in objective and subjective cognition that persisted up to 12 weeks after the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have evaluated the cognitive effects of acupuncture, 85‐88 but to the best of our knowledge few have been conducted in cancer populations. In a randomized controlled trial of 80 Chinese patients with breast cancer who were undergoing chemotherapy, 40 acupuncture significantly improved subjective cognitive function (as measured by the Functional Assessment of Cancer Therapy–Cognitive Function [FACT‐Cog]) and objective cognitive performance (as measured by the Rey Auditory‐Verbal Learning Test and clock drawing test) compared with usual care; however, the durability of these effects after treatment was not assessed. The current study found that acupuncture produced significant, small to moderate improvements in objective and subjective cognition that persisted up to 12 weeks after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that acupuncture produced significant, small to moderate improvements in objective and subjective cognition that persisted up to 12 weeks after the intervention. In the Chinese trial described above, acupuncture also produced a significant increase in serum brain‐derived neurotrophic factor (BDNF) compared with usual‐care controls; the change in BDNF correlated with improvements in cognitive function 40 . Given its hippocampal expression, 89,90 BDNF has been hypothesized to regulate key cognitive processes such as learning and memory, and also is thought to be involved in sleep homeostasis 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…The present meta-analysis included 5 studies 14,17,27,29,34 in which all patients underwent different postoperative chemotherapy regimens (CMF regimens, anthracyclines + paclitaxel or CMF + anthracyclines + paclitaxel) within 1 to 6 months of their recruitment. Critically, cytotoxic reactions to chemotherapeutic agents and somatic immune damage may affect appetite and intestinal motility to varying degrees.…”
Section: Physical Parametersmentioning
confidence: 99%
“…The results of previous studies were inconsistent and controversial. 14 , 18 Therefore, assessing the effectiveness of acupuncture in the management of hormone therapy–related side effects in breast cancer by conducting a systematic review is valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery, radiotherapy, and chemotherapy have improved the survival of patients with BC. There is evidence that chemotherapy induces cognitive impairments including memory impairment, attention deficit, and executive dysfunction in patients with BC (Tong et al, 2018). These cognitive impairments affect long-term quality of life.…”
Section: Introductionmentioning
confidence: 99%